Case Report: Violent Death caused by a Projectile from a Pneumatic Weapon in Soacha, Colombia, 2015 (2016)
Purpose: pneumatic weapon wounds do not represent a significant place in the Colombian Health System statistics. This type of weapons is not globally subjected to legal regulation. Intervention processes are required in the social aspect and strict laws governing the use of these weapons considered toys. Topics: in the medical literature, event mortality is reported with little or no frequency. Most non-fatal cases reported in children with this type of injuries require surgical treatment, usually for the affectation of large vessels or the hemopericardium. Development: the case of a male cadaver is reported, which has a wound from a pneumatic gun in the left breast region.  The circumstances in which the events took place are unknown at the time of removal of the cadaver; he was admitted to the hospital without vital signs. Conclusions: pneumatic weapons are potentially lethal weapons. Pneumatic weapons and their variations are especially found in the hands of children and adolescents, who also make up the majority of victims. Fatal and non-fatal injuries caused by projectiles from pneumatic or similar weapons represent a global public health problem, given the high costs of care, diagnosis, treatment and hospitalization time. Awareness must be raised among decision makers, academia, research centers and health institution about the risks derived from this type of toy.